2019
DOI: 10.1111/cob.12329
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of barriers to effective obesity management in Canada: Results from the ACTION study

Abstract: Summary Obesity is a chronic disease with a significant and growing impact on Canadians. The “Awareness, Care and Treatment In Obesity MaNagement” (ACTION) Study investigated perceptions, attitudes and perceived barriers to obesity management among Canadian people with obesity (PwO), healthcare providers (HCPs) and employers. In this study adult PwO (body mass index ≥30 kg/m2, based on self‐reported height/weight), HCPs (physicians and allied HCPs managing PwO) and employers (≥20 employees; offering health ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
73
4
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(108 citation statements)
references
References 43 publications
15
73
4
4
Order By: Relevance
“…Similarly, few PwO recognize that their HCP has a responsibility to actively contribute to their weight‐loss efforts (range, 21%‐36%) (15,16,20‐22). This is in stark contrast to the responses from HCPs; in Mexico, 92% of HCPs acknowledged their responsibility, compared with 76% to 83% of HCPs in the other ACTION‐IO cohorts (16,20‐22), 72% of HCPs in the ACTION US cohorts (14), and 78% of HCPs in the ACTION Canada cohort (15). PwO assuming full responsibility for weight management is a form of weight‐bias internalization, whereby PwO blame themselves; this is particularly concerning considering that weight stigma, including self‐directed stigma, has been shown to be harmful to mental health and is associated with exercise avoidance and unhealthy eating (23).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, few PwO recognize that their HCP has a responsibility to actively contribute to their weight‐loss efforts (range, 21%‐36%) (15,16,20‐22). This is in stark contrast to the responses from HCPs; in Mexico, 92% of HCPs acknowledged their responsibility, compared with 76% to 83% of HCPs in the other ACTION‐IO cohorts (16,20‐22), 72% of HCPs in the ACTION US cohorts (14), and 78% of HCPs in the ACTION Canada cohort (15). PwO assuming full responsibility for weight management is a form of weight‐bias internalization, whereby PwO blame themselves; this is particularly concerning considering that weight stigma, including self‐directed stigma, has been shown to be harmful to mental health and is associated with exercise avoidance and unhealthy eating (23).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of what can be done to counteract these physiological factors promoting weight regain, studies have suggested that the long-term adoption of behaviors that promote reducing energy intake and increasing energy expenditure (particularly self-monitoring of weight and eating, and cognitive/psychological behaviors such as self-efficacy for weight management and self-efficacy for exercise) may help to avoid regain ( 29 , 30 ). Long-term behavior change, however, may be difficult to achieve, thus the problem of weight regain remains significant within the field of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The survey was conducted by a third-party vendor (KJT Group [Honeoye Falls, NY, USA]); Israeli responses were collected between August 27, 2018 and October 22, 2018. The ACTION-IO study was designed by the study steering committee (including medical doctors employed by Novo Nordisk), with support from KJT Group, and based on ACTION US [ 8 ] and ACTION Canada [ 9 ]. To avoid bias, questionnaire items were carefully phrased and presented in the same order for each respondent and items in a list were displayed alphabetically, categorically, chronologically or randomly, as relevant for each response set.…”
Section: Methodsmentioning
confidence: 99%